Research on Insulation Protective Coatings for Pantograph Assemble Position of Urban Rail Vehicle - ZHOU Sheng; ZENG Fanhui; WANG Haoxin; ZENG Zhi; XING Guohua (机车电传动)
The elastic insulation coatings were developed by using polyether modified resin as binder. The insulation protective coatings for pantograph assemble position of urban rail vehicle was designed with elastic insulation coatings as host. The effect of resins, additives and thickness of elastic insulation coatings on electrical performance, anti-combustibility capability, stain resistant performance, thick painting application properties were investigated. The results shows that electric strength, volume resistivity, water contact angle and anti-combustibility capability of the insulation coatings can reach 32 kV/mm, 3.5×1013Ω·m, 133.8° and requirements for S4, SR2, ST2 and FED<1 specified in DIN 5510, respectively, when the coating is selected a certain resin, phosphorous retardant and modified silicone oil. When a dry insulation coating layer with thickness of over 3.07 mm is obtained, electrical performance of the insulation coatings can meet rule requirements for "GB 10411 DC traction power supply system for urban rail transit".